2011
DOI: 10.1371/journal.pone.0029196
|View full text |Cite
|
Sign up to set email alerts
|

An Immunoassay for Dibutyl Phthalate Based on Direct Hapten Linkage to the Polystyrene Surface of Microtiter Plates

Abstract: BackgroundDibutyl phthalate (DBP) is predominantly used as a plasticizer inplastics to make them flexible. Extensive use of phthalates in both industrial processes and other consumer products has resulted in the ubiquitous presence of phthalates in the environment. In order to better determine the level of pollution in the environment and evaluate the potential adverse effects of exposure to DBP, immunoassay for DBP was developed.Methodology/Principal FindingsA monoclonal antibody specific to DBP was produced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…In Germany, a recent survey on the prevalence of Fusarium species showed that F. graminearum (Fg) and F. verticillioides (Fv) were dominant, their relative occurrence depending on temperature and humidity (Pfordt et al 2020 ). F. graminearum (sexual stage: Gibberella zeae ) causes Gibberella ear rot (GER) which reduces the quantity and quality of maize kernels and more importantly, contaminates the grains with mycotoxins such as deoxynivalenol (DON) and zearalenone (ZON) (Trail 2009 ; Ding et al 2011 ; Martin et al 2012a ; Mesterházy et al 2012 ). These mycotoxins are associated with serious health problems such as kidney diseases, poor growth, and disorders of reproduction in animals and humans (Pinton and Oswald 2014 ; Zhou et al 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…In Germany, a recent survey on the prevalence of Fusarium species showed that F. graminearum (Fg) and F. verticillioides (Fv) were dominant, their relative occurrence depending on temperature and humidity (Pfordt et al 2020 ). F. graminearum (sexual stage: Gibberella zeae ) causes Gibberella ear rot (GER) which reduces the quantity and quality of maize kernels and more importantly, contaminates the grains with mycotoxins such as deoxynivalenol (DON) and zearalenone (ZON) (Trail 2009 ; Ding et al 2011 ; Martin et al 2012a ; Mesterházy et al 2012 ). These mycotoxins are associated with serious health problems such as kidney diseases, poor growth, and disorders of reproduction in animals and humans (Pinton and Oswald 2014 ; Zhou et al 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Based on the problems mentioned above, we have developed an indirect competitive enzyme-based immunoassay strategy for PAE detection. Thus, we have summed up several indirect competitive enzyme-based immunoassays for PAE detection by conjugating enzyme with the secondary antibody to combine the primary antibody (Kuang et al, 2010(Kuang et al, , 2013Wei et al, 2011). This strategy effectively economizes the amount of the primary antibody and decreases non-specific adsorption and strengthens the sensitivity of the immunoassay (Li et al, 2019;Tang et al, 2015).…”
Section: Indirect Competitive Enzyme-based Immunoassay Strategies For Pae Detectionmentioning
confidence: 99%
“…[10][11][12][13][14] Nevertheless, polyclonal antibody is restricted by immunized animals and cannot be produced unlimitedly. 15 Furthermore, it is difficult to produce a broad spectrum antibody that can recognize the whole group of PAEs. Hence, a fast and multi-residue method using relatively inexpensive equipment is desired for the high throughput screening (HTS) of PAEs.…”
Section: Introductionmentioning
confidence: 99%